2022
DOI: 10.1002/aenm.202203573
|View full text |Cite
|
Sign up to set email alerts
|

Lithiophilic Wetting Agent Inducing Interfacial Fluorination for Long‐Lifespan Anode‐Free Lithium Metal Batteries

Abstract: Anode‐free Li metal batteries (AFLMBs) are highly advantageous due to their high energy density, low cost, and simple fabrication. However, severe challenges, such as uncontrolled dendrite formation and low coulombic efficiency, restrict their practical application. Herein, this work introduces a silver nanoparticles incorporated p‐doped conjugated polymer (Ag‐PCP) wetting agent on the copper current collector, which promotes both uniform Li nucleation and rapid formation of a LiF‐rich solid electrolyte interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…can be smaller or even offset which means a smaller overpotential. 70–72 The experimental proof is further shown in Fig. S2 (ESI†).…”
Section: Discussionmentioning
confidence: 92%
“…can be smaller or even offset which means a smaller overpotential. 70–72 The experimental proof is further shown in Fig. S2 (ESI†).…”
Section: Discussionmentioning
confidence: 92%
“…Lithiophilicity is an important factor in the design of the hosts of LMBs, which is mainly achieved by strong affinity with Li. , Numerous studies have demonstrated that functional groups such as −CN, −O, −F, −OH, −COOH, , active compounds such as Ag, Au, Zn, Si, SiO 2 , and ZnO are all lithiophilic. Generally, Li metal hosts with high lithiophilicity can minimize the Li nucleation overpotential and efficiently boost the Li + flux, resulting in good Li + conductivity of the hosts.…”
Section: Gradient Structure Designmentioning
confidence: 99%
“…54 Based on the fundamental theory of the ionovoltaics, the potential for developing novel biological/chemical sensing platforms and improving the performance of lithium-ion batteries and neuromorphic devices was confirmed. 51,52,[55][56][57][58][59][60] The fundamental principle of the continuous energy generation phenomenon by the ionic interfacial interactions in porous structures is still an unresolved question, leading some researchers to speculate that it is a phenomenon similar to streaming potential. 12,[22][23][24] On the contrary, the established theory of ionovoltaics and the exploration of the voltage drop effect due to the 42 resistance of semiconductor electrodes were utilized as a fundamental theory for interpreting the core driving principle of the device.…”
Section: Theoretical Aspectsmentioning
confidence: 99%